2010
DOI: 10.1007/s10067-010-1606-0
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus, human papillomavirus infection, cervical pre-malignant and malignant lesions: a systematic review

Abstract: The purpose of this study was to review and evaluate systematically the scientific evidence on the relationship between systemic lupus erythematosus (SLE), human papillomavirus (HPV) infection, pre-cancerous cervical abnormalities, and cervical cancer. Establishing strict inclusion and exclusion criteria, we performed an extensive search for studies in MEDLINE and BIREME databases to assess the studies that evaluated the frequency of HPV infection, pre-cancerous cervical abnormalities, and cervical cancer in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 32 publications
(40 reference statements)
3
77
0
4
Order By: Relevance
“…Some of the previous studies have shown an increased prevalence of genital HPV infection in patients with SLE [14,15]. Similarly, the four selected articles for this review also showed a high prevalence of CW in SLE patients compared to the control group.…”
Section: Discussionsupporting
confidence: 58%
“…Some of the previous studies have shown an increased prevalence of genital HPV infection in patients with SLE [14,15]. Similarly, the four selected articles for this review also showed a high prevalence of CW in SLE patients compared to the control group.…”
Section: Discussionsupporting
confidence: 58%
“…[73][74][75] A relationship between cervical abnormalities and previous use of immunosuppressive drugs, particularly those exposed to cyclophosphamide in a cumulative dose-dependent way, has been reported. 76,77 Thus, a preventive counseling about cancer surveillance appears relevant in sexually active patients with SLE who receive immunosuppressive therapy, and gynecologic visits at shorter intervals than in general population seem to be a reasonable approach in these patients.…”
Section: 47mentioning
confidence: 99%
“…These immunological abnormalities and the highest exposure to risk factors common to HTLV-1 and HPV could explain the high prevalence of HPV infection 31 . Other immunosuppressive diseases are also associated with a high prevalence of HPV infection, such as HIV infection 20 and systemic lupus erythematosus 32 . However, no difference was found in the proportion of CD4-T lymphocytes and in the HTLV-1 proviral load of HTLV-1-infected patients with HPV, compared with HTLV-1-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…infection among HTLV-infected and uninfected groups when women were stratified into age ranges (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 36-45, 46-55, and 56-65 years). Four positive cases of HPV infection (18.2%) were observed in HTLV-infected women with 46-55 years, whereas none was found in the control group at same age (p = 0.31) (data not shown).…”
Section: Ethical Considerationsmentioning
confidence: 99%